1981
DOI: 10.21273/jashs.106.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Gene Dose Effects on Cane Thorn Density and Cotyledonary Gland Number in Tetraploid Blackberries1

Abstract: Fourteen tetraploid seedling populations of blackberry (Rubus sp.), representing quadruplex, (TTTT), triplex (TTTt), duplex (TTtt), simplex (Tttt), and nulliplex (tttt) genotypes for the major gene conferring thorniness, were evaluated for segregation of cane thorn density and cotyledonary gland number. Comparisons of seedling distribution curves, means and variances of segregating and non-segregating populations did not show a gene dose effect on gland and thorn occurrence. Inheritance of cotyledonary glands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Thorn lessness in 'Merton Thornless' and its derivatives is conditioned by a single gene with the thornless condition expressed in the homo zygous recessive state (18). Pavlis and Moore (17) recently showed that the inheritance of thorns in 'Merton Thornless' derivatives is qualitative, but the density of thorns on thorny segregates is con trolled by several modifying genes. Thorn size, shape, and density vary widely among R ubus species (Fig.…”
Section: Thornlessnessmentioning
confidence: 99%
“…Thorn lessness in 'Merton Thornless' and its derivatives is conditioned by a single gene with the thornless condition expressed in the homo zygous recessive state (18). Pavlis and Moore (17) recently showed that the inheritance of thorns in 'Merton Thornless' derivatives is qualitative, but the density of thorns on thorny segregates is con trolled by several modifying genes. Thorn size, shape, and density vary widely among R ubus species (Fig.…”
Section: Thornlessnessmentioning
confidence: 99%